Persepsi Pelanggan terhadap Keberlanjutan Pelayanan Sistem Penyediaan Air Minum (Spam) di Kabupaten Purwakarta - Hidayatul Lailiah; Zainal Abidin; Fembriarti Erry Prasmatiwi; Muhammad Irfan Affandi; Maya Riantini (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the improvement of Drinking Water Supply System (SPAM) services in Purwakarta Regency by examining current service conditions, customer perceptions, and factors influencing those perceptions. The study employed a survey method using purposive sampling, involving 100 household respondents from the three areas with the highest number of SPAM customers: Nageri Kaler, Ciseureuh, and Nageri Kidul. Data were analyzed using SmartPLS through the Partial Least Squares (PLS) technique. The results indicate that SPAM services in Purwakarta Regency remain suboptimal. The piped water services provided by Perumda Air Minum Gapura Tirta Rahayu show limited technical service coverage, low customer growth, and low water consumption. Customer perceptions are generally positive, particularly regarding water quality and service availability. Internal user factors, including subscription duration, knowledge, and personal motivation, significantly influence customer perceptions. In contrast, external factors such as income, infrastructure availability, government support, and promotion do not directly affect perceptions, although they contribute to SPAM sustainability. Internal factors also influence sustainability through customer perception as a mediating variable, whereas external factors have no significant indirect effect through customer perception.